(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Supply Chain Performance Analysis of Strawberries (Case Study of Segening Farmer Group, Pancasari Village, Sukasada District, Buleleng Regency). Competition in the horticultural industry, particularly in strawberry commodity, is becoming increasingly intense as market demand rises. The main challenge in the strawberry supply chain is the fluctuation and seasonal nature of strawberry products, which affect availability and quality. This study aims to identify the flow and analyze the performance of the strawberry supply chain sourced from the Segening Farmers Group. The research employs the SCOR method with an AHP (SCOR-AHP) approach to measure supply chain performance. The results indicate that the flow of products, financial flow, and information flow are well integrated. Based on the performance classification, the supply chain is categorized as moderate to good, with a performance scores of 90% at the farmer level, at the collector level 90%, at the wholesaler level 91%, and 89% at the retailer level, indicating potential for improvement. The ranking of performance among the supply chain actors is as follows: wholesalers, collectors, farmers, and retailers. Several indicators that need improvement include product defect rates, delivery time, availability of production facilities, and the ability to fulfill sudden orders.